Indexes of physical development, physical preparedness and functional state of polish students - Prusik Krzysztof; Prusik Katarzyna; Iermakov S.S; Kozina Zh.L (Kharkov National Pedagogical University, 2012)
The purpose of work - determination of level of physical development, physical preparedness and functional state of the Polish students. In research took part 50 students of Higher School of Sciences about a Health from Bydgoshch (14 boys and 36 girls, aged 18-29 years). It is exposed, that the indexes of flexibility correspond the middle indexes of flexibility of spine for people, not going in for sports. The indexes of Index of Kettle correspond a normosthenic build, there are separate cases of failing and surplus of mass of body. It is set that the index of Index Rufe corresponds the satisfactory estimation of capacity. The indexes of test of Romberga testify to the low functional state of vestibular analyzer and low level of static co-ordination. More high indexes of force of the left brush are got as compared to right. It is exposed, that indexes simple a reaction on a sound above average level, indexes of reaction of choice are at satisfactory level, and indexes simple a reaction on light - below the average level. A change of frequency of heart-throbs in an orthostatic test is within the limits of norm. In the system of physical education it is necessary to spare the special attention development of the cardiovascular system and vestibular stability, and also instrumental in the change of appearance life of students toward the increase of their motive activity.